Single-Metal Hybrid Micromotor - Li, Dajian; Zheng, Yuhong; Zhang, Zhanxiang; Zhang, Qi; Huang, Xiaoying; Dong, Renfeng; Cai, Yuepeng; Wang, Lin (Frontiers in Bioengineering and Biotechnology, 2022)
Multi-mode stimuli regulated propulsions are extremely useful for artificial micro-/nanomotors in performing specialized tasks in different microscopic environments. However, it is still a great challenge to develop a simple and efficient micro/nanosystem which can operate in complicated environments, either with fuel or without fuel. Here, we report a novel hybrid micromotor which only needs one metal with a special structure: micro-spherical shell with a hole. Since we attractively combine the inherently catalytic properties of Pt for chemical propulsion with a designed concave structure for acoustic propulsion, the micromotors can not only move rapidly in H2O2 fueled environment due to the chemical reaction between Pt and H2O2, but also can exhibit excellent acoustic propulsion in fuel-free environment due to the non-uniform stress caused by ultrasound. In addition, attractive group motion behavior of the motors, including aggregation, group migration and dispersion, are easily realized by acoustic field regulation. The brand-new single-metal hybrid micromotors with dual driving mode, flexible propulsion regulation and efficient group motion regulation, which are essential for making micro-/nanomotors compatible with different surrounding environments, are expected to advance the field of artificial nanomachines.